2016
DOI: 10.1002/jsfa.7755
|View full text |Cite
|
Sign up to set email alerts
|

Determination of four different purines and their content change in seafood by high-performance liquid chromatography

Abstract: The purine content of seafood differed depending on species, body part and degree of freshness, which could recommend consumers a healthy diet, especially for people with hyperuricemia and gout. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
(56 reference statements)
2
11
0
Order By: Relevance
“…Furthermore, all muscle samples (dorsal muscles and abdominal muscles) were found to contain higher amounts of hypoxanthine than the other three purine bases. This observation is consistent with the report by Qu et al, (2017), who found that hypoxanthine content was the dominant purine in the muscles of Lateolabrax japonicus , followed by adenine, guanine, and xanthine.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, all muscle samples (dorsal muscles and abdominal muscles) were found to contain higher amounts of hypoxanthine than the other three purine bases. This observation is consistent with the report by Qu et al, (2017), who found that hypoxanthine content was the dominant purine in the muscles of Lateolabrax japonicus , followed by adenine, guanine, and xanthine.…”
Section: Resultssupporting
confidence: 93%
“…Other studies have investigated the purine contents of vegetarian meat analogues, beer, beer-like alcoholic beverages, pork, and beef via HPLC (Havlik et al, 2010; Fukuuchi et al, 2013; Rong et al, 2015). Nevertheless, few HPLC methods have been used to quantify the adenine, guanine, hypoxanthine, and xanthine contents in marine fish (Qu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the purine removal rate could be significantly increased after soaking with allicin and then boiling. As shown in Figure 1, muscle sample mainly contained hypoxanthine, which was consistent with the results of Qu, Sui, Mi, and Lin (2016). Therefore, the change in the content of hypoxanthine has a significant effect on the total purine content.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, adenine and hypoxanthine had a greater hyperuricemic effect [17]. Differences in the metabolic effect of individual purine base would suggest that the restriction of some foods should be based on the content of uricogenic purines rather than on the total purine content [1]- [3]. Overall, the mushroom fruit body contains mainly adenine and xanthine, and xanthine does not tend to elevate serum concentration of uric acid.…”
Section: A Purine Content In Fruiting Bodiesmentioning
confidence: 99%
“…Dietary purines, including adenine, guanine, hypoxanthine and xanthine, occur widely in food as constituents of nucleic acids, nucleotides and free bases [1]- [3]. The end product of purine metabolism is uric acid, and the increase of serum uric acid level causes gout and hyperuricemia [4]- [7].…”
Section: Introductionmentioning
confidence: 99%